Absenteeism-disease in university employees: a cross-sectional study of the reasons for leave from 2013 to 2018 - Pinto, Carolina de Mendonça Brandão; Moreira, Tiago Ricardo; Ferreira, Débora Carvalho; Franceschini, Sylvia do Carmo Castro; Henriques, Bruno David (Ciência e Natura, 2022)
The Server’s Integrated Health Subsystem is used to register health treatment licenses in the Federal Public Service, enabling knowledge about absenteeism-illness. To subsidize health promotion actions, it is intended to know its motivating causes in a Federal Education Institution in Minas Gerais. A cross-sectional study on leave between 2013 and 2018 was carried out. The variables were: position, sex, number of days off and the motivating code of the leave. Descriptive and inferential analyzes were performed using Poisson Regression. The main motivations found were: musculoskeletal disorders, followed by mental health in the group of professors and respiratory disorders in the group of administrative technicians, among whom, technicians up to 50 years old are associated with sick leave due to respiratory tract disorders and civil servants over 50 years old for musculoskeletal reasons. There was no difference in age with regard to mental disorder in this group. The static ergonomic risk associated with respiratory and psychic outcomes, and the risk due to dynamic activities in the absence of musculoskeletal disorders. Based on the data presented, it is possible to propose measures for Health Policy, aimed at improving the environment and work process, minimizing its risks and protecting the health of the employee.